2005
DOI: 10.1037/0022-3514.88.3.510
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Conflict and Support in Romantic Relationships: The Role of Attachment Anxiety.

Abstract: Guided by attachment theory, a 2-part study was conducted to test how perceptions of relationship-based conflict and support are associated with relationship satisfaction/closeness and future quality. Dating partners completed diaries for 14 days (Part 1) and then were videotaped while discussing a major problem that occurred during the diary study (Part 2). Part 1 reveals that more anxiously attached individuals perceived more conflict with their dating partners and reported a tendency for conflicts to escala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

43
584
3
10

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 614 publications
(640 citation statements)
references
References 69 publications
43
584
3
10
Order By: Relevance
“…It seems likely that evidence and feedback play some role in updating expectancies. Expectancies also likely have some deeper core tracing back to basic working models for the self, others, and relationships that are built up over the course of a lifetime (e.g., Campbell, Simpson, Boldry, & Kashy, 2005). Baldwin and Keelan (1999) argued that individuals higher in trait self-esteem had more positive interpersonal expectancies about their own ability to secure affiliation from others.…”
Section: Lessons For Studying Assertiveness Expectanciesmentioning
confidence: 99%
“…It seems likely that evidence and feedback play some role in updating expectancies. Expectancies also likely have some deeper core tracing back to basic working models for the self, others, and relationships that are built up over the course of a lifetime (e.g., Campbell, Simpson, Boldry, & Kashy, 2005). Baldwin and Keelan (1999) argued that individuals higher in trait self-esteem had more positive interpersonal expectancies about their own ability to secure affiliation from others.…”
Section: Lessons For Studying Assertiveness Expectanciesmentioning
confidence: 99%
“…Research on adult attachment has shown that anxiously attached individuals tend to interpret their partners' conflict behavior more negatively than securely attached individuals (Campbell, Simpson, Boldry, & Kashy, 2005;Simpson, Rholes, & Phillips, 1996), which can then affect conflict behavior. Similarly, those who do not feel valued by their partners respond more negatively to relationship threats (Murray, Bellavia, Rose, & Griffin, 2003), and these insecure individuals often express their insecurities to their partners, further threatening the relationship (Lemay & Clark, 2008;Murray et al, 2003).…”
Section: Relational Conflict and Verification/enhancement Processesmentioning
confidence: 99%
“…That is, our test of the proposition that attachment style would predict couple interactions was prospective. Earlier studies tended to look only at the association between attachment style and couple interactions at the same point in time (e.g., Campbell, Simpson, Boldry, & Kashy, 2005;Simpson, Rholes, & Phillips, 1996;Tucker & Anders, 1998), a research strategy less able to evaluate the direction of hypothesized effects. In any case, the present findings clearly demonstrate the significance of behavioral interactions in close relations in predicting romantic attachment security.…”
Section: Discussionmentioning
confidence: 99%